THE ROLE OF CONSUMER TRUST IN MEDIATING WEBSITE QUALITY TO THE PURCHASE INTENTION ON ZILINGO ONLINE SHOP SITE IN BANDAR LAMPUNG - Atikah Nur Hidayah; Faila Shofa (Metakom, 2019)
The purpose of the research was to determine the role of consumer trust in mediating website quality to the purchase intention on zilingo online shop site in Bandar Lampung. This type of research is an associative quantitative approach. The population of this study is the people domiciled in Bandar Lampung who have visited the website of the Zilingo website. Data collection techniques with a questionnaire of 100 respondents. Validity testing uses factor analysis and reliability testing using Cronbach's Alpa. The data analysis technique uses path analysis with the SPSS program. The results of the research website quality variables have a positive effect on purchase intention indirectly through trust in online shopping sites Zilingo.com in Bandar Lampung by 30% while the remaining 70% is influenced by other variables. Keywords: Website Quality, Trust, Purchase Intention